Analisis Bibliometrik: Faktor yang Mempengaruhi Penggunaan E-Form Terhadap Pelaporan Surat Pemberitahuan (SPT) Tahunan Berbasis Vosviewer - Masyaila Laurensa Zuhri; Wahyu Helmy Dimayanti Sukiswo (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The aim of the research is to map the development of literature discussing the use of E-Form for reporting annual notification letters (SPT). Apart from that, other authors can also get new keywords that can be developed for further research. The method used is bibliometric analysis with the VOSviewer application. Literature was obtained from Publish or Perish covering the years 2019-2024 and there were 86 articles out of 200 articles that had been sorted according to the criteria. The results obtained from the research are that the use of the e-form system is influenced by the convenience, usefulness and compliance of taxpayers in reporting taxes with notification letters (SPT) via e-SPT. New keywords that have the potential for further research are digitalization, e-system, and tax education.